Secure Cryptographic Key Encapsulation and Recovery Scheme in Noisy Network Conditions - Dina Ghanai Miandoab; Michael Logan Garrett; Mahafujul Alam; Saloni Jain; Sareh Assiri; Bertrand Cambou (Applied Sciences)
In this study, we present the Response-Based Key Encapsulation Mechanism (R-KEM), an ephemeral key encapsulation and recovery scheme tailored for cryptographic systems in high-noise, high-jamming network environments. By adopting the Challenge–Response Pair (CRP) mechanism for both key encapsulation and authentication, R-KEM eliminates the need to store secret keys on the device, favoring on-demand key generation. By maintaining only encrypted data on the device, R-KEM significantly enhances security, ensuring that in the event of an attack, no sensitive information can be compromised. Its novel error-correcting strategy efficiently corrects 20 to 23 bits of errors promptly, eliminating the need for redundant helper data and fuzzy extractors. R-KEM is ideally suited for terminal devices with constrained computational resources. Our comprehensive performance analysis underscores R-KEM’s ability to recover error-free cryptographic keys in noisy networks, offering a superior alternative to conventional methods that struggle to maintain secure data transmission under such challenges. This work not only demonstrates R-KEM’s efficacy but also paves the way for more resilient cryptographic systems in noise-prone environments.